2021
DOI: 10.1002/jcb.30176
|View full text |Cite
|
Sign up to set email alerts
|

Myricetin inhibits breast and lung cancer cells proliferation via inhibiting MARK4

Abstract: Identifying novel molecules as potential kinase inhibitors are gaining significant attention globally. The present study suggests Myricetin as a potential inhibitor of microtubule‐affinity regulating kinase (MARK4), adding another molecule to the existing list of anticancer therapeutics. MARK4 regulates initial cell division steps and is a potent druggable target for various cancers. Structure‐based docking with 100 ns molecular dynamics simulation depicted activity of Myricetin in the active site pocket of MA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 70 publications
(78 reference statements)
1
22
0
Order By: Relevance
“…All these binding experiments were conducted at physiological pH of 7.4. The obtained quenching data were put into Stern-Volmer (Equation ( 1)) and modified Stern-Volmer equation (Equation ( 2)) as per earlier published literature [20,21,36] to find various binding parameters. The binding experiment was performed at physiological pH of 7.4.…”
Section: Steady-state Fluorescencementioning
confidence: 99%
See 1 more Smart Citation
“…All these binding experiments were conducted at physiological pH of 7.4. The obtained quenching data were put into Stern-Volmer (Equation ( 1)) and modified Stern-Volmer equation (Equation ( 2)) as per earlier published literature [20,21,36] to find various binding parameters. The binding experiment was performed at physiological pH of 7.4.…”
Section: Steady-state Fluorescencementioning
confidence: 99%
“…Investigations have shown that α-amylase inhibition aids in regulating glucose levels [17]. Polyphenols, their derivatives and other naturally derived compounds show therapeutic potential against various diseases such as cancer [18][19][20][21], neurodegenerative disorders [22,23], diabetes [24,25] and many more.…”
Section: Introductionmentioning
confidence: 99%
“…Natural products are extensively used to target cancer therapy with minimal side effects ( Anwar et al, 2020a ; Anwar et al, 2020b ; Anjum et al, 2021 ; Anwar et al, 2021 ; Anwar et al, 2022a ; Anwar et al, 2022b ; Anwar et al, 2022c ). Cinnamomum zeylanicum (CZ) is a tropical evergreen plant belonging to the genus Cinnamomum.…”
Section: Introductionmentioning
confidence: 99%
“…BC is often detected in its advanced stages when the available treatment is not very effective [ 1 ]. There are many studies that have searched for new methods of BC treatment, e.g., by inhibiting kinases such as MARK4 [ 2 , 3 ]; however, there is still a need to search for new potential drugs and prognostic and predictive markers for BC. Recent studies on BC and other cancer types have indicated that irisin could be one such potential marker.…”
Section: Introductionmentioning
confidence: 99%